Ethnobotanical study on the different use forms of Cannabis sativa L. in the provinces of Al-Hoceima and Chefchaouen (Northern Morocco) - Hourmate Allah, Maria; Redouan, Fatima Zahrae; Merzouki , Ghizlane; Merzouki, Abderrahmane (Ethnobotany Research and Applications, 2025)
Background: Cannabis sativa L. was among the first plants used by humans for fiber, food, medicine, and in sociocultural settings. This study aimed to identify the local uses of Cannabis sativa L. and its socio-cultural importance in the provinces of Al-Hoceima and Chefchaouen in Northern Morocco. Methods: The survey was conducted between September 2023 and May 2024 using semi-structured questionnaires in the provinces of Al-Hoceima and Chefchaouen. Results: The values of the diversity and equitability knowledge indices are high (ID>5 and IE>0.5) indicating an equal distribution of knowledge among the respondents about Cannabis sativa L. Five types of use of the species were identified: economic, psychoactive, traditional medicine, cosmetics and fodder. The most commonly used plant parts are leaves, flowers and seeds. Chi-square and ANOVA tests using SPSS software revealed a slight variation in knowledge of the use of the species according to sex and age. The plant part uses values calculated by age category and gender were subjected to multiple correspondence analysis (MCA). Conclusion: The population of the provinces of Al-Hoceima and Chefchaouen is mainly dependent on cannabis cultivation for their livelihood, with the majority of males using the plant for psychoactive purposes. One of the goals of legalizing Cannabis in Morocco is to increase the value of the plant by diversifying its legal uses. Keywords: Ethnobotanical knowledge, survey, Cannabis sativa L., Northern Morocco, semi-structured questionnaires.